THE ANTHROPOCENE OR THE ‘END’ OF THE IMPERATIVE RESPONSIBILITY - Cera, Agostino (Pensando - Revista de Filosofia, 2020)
My paper aims to sketch the Paradox of Omni-responsibility, namely the ethical paradox that emerges from the so-called Anthropocene considered as our current epochal framework. The main outcome of this paradox is the overcoming of Hans Jonas’s principle/imperative responsibility as an ethical standard for ecological (and more generally, philosophical) thought over recent decades. if the imperative responsibility has been the cornerstone of an “ethics for the technological age”, it probably cannot play the same role in the anthropocenic/technocenic age. My argument proceeds as follows. The first stage deals with a critical dissection of the Anthropocene as “discourse” (§ 1); the second stage introduces the Pet-tification of Nature (i.e. the characterization of the planetary organism as a pet), the Aidosean Prometheanism (i.e. a new form of anthropocentrism) and the Paradox of Omni-responsibility as basic outcomes of the anthropocenic framework (§ 2); in the third and final stage, I will draw my conclusions concerning the redefinition of Anthropo-cene as Techno-cene and the proposal of a renewed ethical dialogue between responsibility and releasement, that is between Jonas and Heidegger (§ 3).